A TEACHER'S STORY OF FACING THE ROAD OF CHANGE (Polifonia, 2012)
This paper aims at discussing some difficulties to promotechanges in the established landscape of Education. This paper is mainlydeveloped based on some experiences concerned to language teachingin undergraduate course level of a Brazilian University Center. I intendto draw a picture of such difficulties through some stories to live by,having in mind possibilities of changing on the teaching and learningprocess and also on the research language. As my aim is connected tothe idea of changing, the way I assume a narrative writing is importantto some aspects addressed throughout the paper.KEYWORDS: narrative, changes, language teachingA HISTÓRIA DE UMA PROFESSORA AO ENFRENTAR O CAMINHO DA MUDANÇARESUMO: Neste artigo tenho como objetivo discutir algumas dificuldadespara promover transformações em nossa paisagem educacional. Oartigo se originou do estudo de experiências relacionadas ao ensino delínguas em um curso de graduação de um Centro Universitário Brasileiro.Pretendo compor um cenário dessas dificuldades, por meio do contarde histórias vividas, considerando algumas possibilidades de transformaçãono processo de ensino e aprendizagem e, também, na linguagemutilizada em nossas pesquisas. Assim, como meu objetivo está relacionadoà idéia de mudança, a forma como assumo uma escrita narrativaé importante para alguns aspectos tratados ao longo do artigo.PALAVRAS-CHAVE: narrativa, transformação, ensino de língua